Analisis Konsep Sustainability Management (SM) Dan Filantropi Di PT. Astra Internasional Tbk - Muna Irtiyah (Sociale : Journal of Social Science, 2026)
This study aims to analyze the implementation of Sustainability Management (SM) and philanthropic practices carried out by PT Astra International Tbk as part of the company's sustainability strategy. In the modern business context, sustainability is not only an external demand, but also an integral part of long-term competitive advantage. This study uses a descriptive qualitative approach with data collection techniques through document studies, indirect observations, and semi-structured interviews with relevant stakeholders. Data sources consist of company sustainability reports, academic publications, and information from trusted media. The results show that Astra has successfully integrated sustainability principles into its business operations through programs that cover environmental, social, and governance aspects. Initiatives such as the development of environmentally friendly vehicles, community empowerment through vocational education, and the SATU Indonesia Awards program reflect the company's commitment to creating shared value. The philanthropic practices carried out are not only charitable, but also strategic and oriented towards long-term impact. This study concludes that PT Astra International Tbk can be a model for the effective implementation of SM and philanthropy in Indonesia.